MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID MELALUI PENGGUNAAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS IDEAL PROBLEM SOLVING DI KELAS XI MIA 3 SMAN 1 PEKANBARU - Ermei Hijjah Handayani; Elva Yasmi Amran; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Classroom action research had been done on student learning activity on Colloid subject in XI MIA 3 of SMAN 1 Pekanbaru. This research was conducted by using student worksheet that is based on IDEAL Problem Solving. Student learning activity which is repaired the activity of asking question, submit answers or opinions, doing student worksheet is based on IDEAL Problem Solving and group discussion. This research consisted of two cycles. Each cycle consisted of two meetings that went through four stages of implementation: planning, action, observation, and reflection. Data collection technique use observation test and questionnaire . The result of action showed that learning activity percentage of student improved and reached the success indicator. The learning activity of student percentage in first cycle is 61,33% with enough category and second cycle is 73,86% with good category. Based on the result obtained, it can be concluded the using of student worksheet that is based on IDEAL Problem Solving can improve student learning activity.Keyword :Student Worksheet That is Based On IDEAL Problem Solving, Student Learning Activity, Colloid